Revisión de literatura sobre la aplicación de la Teoría Unificada de Aceptación y Uso de Tecnologías en gobiernos electrónicos - Machado de Freitas, Marcelo (2022)
Governments are spending a considerable amount of resources to digitalize their many services. The purpose of this research was to conduct a systematic review of e-Government acceptance papers that used the Unified Theory of Acceptance and Use of Technologies (UTAUT) as the theoretical background. From the 1529 articles using UTAUT (from 2003 to 2019), we selected the 41 most cited papers that were related to e-Government acceptance. All 41 articles were fully read to understand research gaps. We found that only a few studies have been faithful to the original UTAUT model. Although improving the theory with new variables is important, the validation of the original model also is. Constructs such as trust, quality of information, quality of service, and quality of the system, despite not being original from UTAUT seminal paper, were often integrated into the model to predict individuals’ behavioral acceptance. Our findings are important to understand that as different technologies have different users and different purposes, different constructs might help to explain the individual behavior about using or not those technologies. By highlighting the research gaps, our paper guides future work on the use of UTAUT as a theoretical lens for the acceptance of e-Government.